2011
DOI: 10.1080/08927014.2011.584619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biofilm formation on membrane performance in submerged membrane bioreactors

Abstract: The effects of biofilm formation on membrane performance were evaluated for a submerged membrane bioreactor (sMBR) system with six different types of micro- and ultrafiltration membranes (working volume=19 l). After operation for 24 h the permeability of the membranes with a larger pore size (microfiltration) decreased to that of the membranes with a much smaller pore size (ultrafiltration). Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) confirmed that biofilms could redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Furthermore, the cake layer acted as a second biological barrier in removing COD. This is in agreement with previous reports which showed that the cake layer can affect COD removal in the iMBR [35]. Figure 2 illustrates application of Hermia's model (2) to different experimental conditions.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the cake layer acted as a second biological barrier in removing COD. This is in agreement with previous reports which showed that the cake layer can affect COD removal in the iMBR [35]. Figure 2 illustrates application of Hermia's model (2) to different experimental conditions.…”
Section: Resultssupporting
confidence: 91%
“…Mixed liquor suspended solids (MLSS), chemical oxygen demand (COD) and sludge relative hydrophobicity (RH) are among the main characteristic parameters of activated sludge suspension that are traditionally monitored in an MBR system [22,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Concentration polarization, external fouling, and internal fouling [120][121][122] Biofouling, organic fouling, and inorganic fouling [123] Reversible, irreversible, residual, and irrecoverable fouling [124] Types Concentration polarization [125,126] Biofouling (biosolids) [131,132] Reversible fouling [136] Irreversible fouling [137] External fouling [127,128] Organic fouling [133,134] Residual fouling [138] Internal fouling [129,130] Inorganic fouling [135] Irrecoverable fouling [139] sheets as the second stage. They discovered that the fouling and flux decline in hybrid membrane methods are influenced directly by the membrane surface characterization.…”
Section: Fouling Reasonsmentioning
confidence: 99%